Regioselective ketalization (dioxane vs dioxolane) study of internal diastereomeric 1,2,3-triol systems obtained from d-pentoses - Chiranjeevi Donthulachitti; Yelukala Ramakrishna; Ravikumar Shekunti; Chandra Kiran Neella (Results in Chemistry, 2022)
Ringselective and regioselective acetonide protection of four diastereomeric triol systems (ribo & xylo with 1,3-syn configuration and arabino & lyxo with 1,3-anti configuration) were studied and certain useful generalizations are drawn as follows. Three triol systems i.e. xylo, arabino and lyxo triol systems have preferred only five membered acetonides (dioxolanes) over six membered acetonides (dioxanes). Selective formation of five membered anti acetonides was noticed when there is a competition between syn and anti acetonide formation. If the acetonides formed from any triol system are either syn or anti, then only allylic acetonides are favoured over non-allylic acetonnides. Only ribo-triol system formed six membered syn acetonides (thermodynamic control). No triol has produced all the three acetonides. All the ring sizes were unambiguously confirmed by employing Evan's 13C NMR method supported by 1H NMR spectroscopy. These chiral building blocks with predefined stereochemistry and multiple functional groups can be potential scaffolds for total synthesis.